(untitled) (Journal of Applied Oral Science, 2009)
The CD-ROM "Voice Assessment: Speech-Language Pathology and Audiology & Medicine" was developed as a teaching tool for people interested in the production of the spoken or sung human voice. Its content comprises several subjects concerning the anatomy and physiology of spoken and sung voice. A careful assessment becomes necessary in order to ensure the effectiveness of teaching and learning educational materials, whether related to education or health, within the proposal of education mediated by technology. OBJECTIVE: This study aimed to evaluate the efficacy of the Virtual Man Project's CD-ROM "Voice Assessment: Speech-Language Pathology and Audiology & Medicine", as a self-learning material, in two different populations: Speech-Language Pathology and Audiology students and Lyrical Singing students. The participants were instructed to study the CD-ROM during 1 month and answer two questionnaires: one before and another one after studying the CD-ROM. The quantitative results were compared statistically by the Student's t-test at a significance level of 5%. RESULTS: Seventeen out of the 28 students who completed the study, were Speech-Language Pathology and Audiology students, while 11 were Lyrical Singing students (dropout rate of 44%). Comparison of the answers to the questionnaires before and after studying the CD-ROM showed a statistically significant increase of the scores for the questionnaire applied after studying the CD-ROM for both Speech-Language Pathology and Audiology and Lyrical Singing students, with p